Recommendations toward a human pathway-based approach to disease research. Issue 11 (November 2018) - Marshall, Lindsay J.; Austin, Christopher P.; Casey, Warren; Fitzpatrick, Suzanne C.; Willett, Catherine
Highlights: International workshop agrees key recommendations to revitalize drug discovery. Exploiting ongoing human-focused efforts will enhance human disease understanding. Incentivized data sharing, standardized data and consistent ontologies are required. Interoperability needs improved interdisciplinary and international collaboration. Global funding calls should prioritize human-based methods, such as organoids. Abstract : Failures in the current paradigm for drug development have resulted in soaring research and development costs and reduced numbers of new drug approvals. Over 90% of new drug programs fail, the majority terminated at the level of Phase 2/3 clinical trials, largely because of efficacy failures or unexplained toxicity. A recent workshop brought together members from research institutions, regulatory agencies, industry, academia, and nongovernmental organizations to discuss how existing programs could be better applied to understanding human biology and improving drug discovery. Recommendations include increased emphasis on human relevance, better access and curation of data, and improved interdisciplinary and international collaboration. Teaser: Improved translation of research is needed to inform safe and effective drug development. This will require a broad collaborative effort, open data sharing, and prioritized funding for human-relevant research.